1998
DOI: 10.1080/11250009809386796
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic study of two species of needlefish (Belonidae) from Argentina

Abstract: The chromosomes of the two species of needlefish, Potamorraphis cf. eigenmanni and Strongylura microps, from fresh waters of Argentina were analyzed using C-banding and silver staining and their karyotypes were described for the first time. The former species possessed 2n -54 and karyotype composed of three pairs metacentric to submetacentric chromosomes and 24 pairs of subtelo to telocentric chromosomes. The NORs were situated on the end of the shorter arms of one middle-sized bi-armed pair of chromosomes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Beloniformes represents a group of marine origin with only two species in the Paraná -Plata river basin (CASTELLO et al 1978;LOVEJOY 2001): Strongylura microps, with 2n=50: 50 ST-A chromosomes and Potamorraphis eigenmanni, with 2n=54: 46 ST-A + 6 M-SM + 2 microchromosomes (PASTORI et al 1998)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beloniformes represents a group of marine origin with only two species in the Paraná -Plata river basin (CASTELLO et al 1978;LOVEJOY 2001): Strongylura microps, with 2n=50: 50 ST-A chromosomes and Potamorraphis eigenmanni, with 2n=54: 46 ST-A + 6 M-SM + 2 microchromosomes (PASTORI et al 1998)…”
Section: Resultsmentioning
confidence: 99%
“…Microchromosomes are not frequently found in neotropical fishes. However 14 of these chromosomal forms were observed in Bujurquina vittata, 2 in Potamorraphis eigenmanni and 1 in Schizodon nasutus (RONCATI et al 2000;PASTORI et al 1998;PASTORI et al 1997, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Among belonids, the heterochromatin can be considered an important component in the karyotype diversification of the group. Pastori et al (1998) have also observed a remarkable pattern in other species, including entirely heterochromatic chromosomes (NOR-bearing and B chromosome).…”
Section: Discussionmentioning
confidence: 76%
“…Studies carried out in the Belonidae family reported karyotypes with two diploid numbers, 48 or 50 chromosomes, varying from all acrocentric chromosomes to diverse karyotypic formulas (Srivastava and Kaura 1964;Rish 1973;Rishi and Singh 1982), including the presence of the supernumerary chromosomes in Strongylura microps (Pastori et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…1[link]). Up to two of these small chromosomes have also been found in Synbranchus marmoratus Bloch, 1795 of the order Synbranchiformes (Sanchez & Fenocchio, 1996 a ) and in Strongylura hubbsi (Collette, 1974) of the order Beloniformes (Pastori et al , 1998) (Table III and Fig. 1[link]).…”
Section: B Chromosomes In the Major Freshwater Fish Ordersmentioning
confidence: 99%